Health education for the community in the prevention of hypertension and stroke - Yoga Tri Wijayanti; Sumiyati Sumiyati; Deviarbi Sakke Tira; M Khalid Fredy Saputra (Edukasi Ilmiah Indonesia, 2024)
Hypertension and stroke are two interrelated health conditions and have a high prevalence in the community. Both diseases can be prevented through effective health education, which aims to increase public awareness and knowledge about risk factors, early signs, and prevention efforts that can be taken. This Community Service Program aims to provide health education to the public about the prevention of hypertension and stroke, with a focus on the introduction of healthy lifestyles, risk factor control, and the importance of early detection. This activity was carried out by involving the active participation of the local community. The methods used in this program include lectures, interactive discussions, and simulation of preventive measures. The educational material includes the importance of dietary regulation, physical activity, stress management, and regular blood pressure monitoring. Program evaluation is carried out through pre-test and post-test to measure the improvement of public knowledge after receiving education. The results of this program show a significant improvement in public understanding of hypertension and stroke prevention. Most participants were able to identify risk factors and express readiness to adopt a healthier lifestyle. Thus, this program is expected to contribute to reducing the incidence of hypertension and stroke in the community through increased awareness and better preventive measures